Sosialisasi Penggunaan Quizizz Sebagai Platform Alternatif Evaluasi Pembelajaran Daring Bagi Guru-guru SDN 1 Tegal Munjul Purwakarta - Sukma Dwi Lestari; Adhana Zulfa Aulia; Annisa Fitria Kusuma; Dinda Irene Septiani; Nanda Zaidah; Santi Sopianti; Acep Ruswan (Indonesian Journal of Community Services in Engineering & Education (IJOCSEE), 2021)
The implementation of online learning requires teachers to be more innovative in finding attractive learning alternatives. One of the digital devices that can be used is the Quizizz application. However, it is not uncommon for the use of digital devices to be quite difficult for some teachers or teachers. The socialization of the use of the Quizizz application is a form of service organized by the students of the Indonesian Education University, Purwakarta Campus, who are carrying out PLSP activities at UPTD SDN 1 Tegal Munjul. The activity begins with taking care of permits and coordinating with the school regarding program targets, namely teaching staff or teachers. Then, the organizers conduct socialization and training using the Quizizz application through the provided zoom meeting link in the core activities. The evaluation of this activity is by using the interview technique through several questions posed on the questionnaire via a google form link distributed to participants after the webinar activity is completed. This series of activities is intended to assist teachers or teachers during the implementation of online learning.